Using the World Wide Web - Eager, Bill (Que, 1994)
The book teach the techniques and terminology through the Internet and the World Wide Web; provides both reviews and in-depth explanations of the most popular WWW brosers; teach how to create a WWW home page; guide how to write HTML, the computer programming language for the WWW. Finally, the main part of this book consists of reviews and listings of the multitude of resources now available on WWW servers around the world